Using Podcasts to Improve Listening and Speaking Skills: Literature Review - Budiasningrum, Retno Setya; Rosita, Rahmi (ASIAN PUBLISHER, 2022)
Listening and speaking are fundamental communication skills. Language learners who study a foreign language need to learn these skills seriously to communicate well. Unfortunately, learning those skills is difficult for them. As podcasts have many benefits for the students, those resources help students to learn the language. The paper discussed how podcasts are helpful for foreign language learners to improve their listening and speaking skills. This literature review indicated several previous studies recommending using podcasts as learning support in improving listening and speaking skills. Keywords: Podcasts, Listening skills, Speaking skills.